Information systems for crisis management - Altschuller, Shoshana S. (Henry Stewart Talks, 2011)
The crisis scenario, During crisis IS supports 4 main functions, Preparedness, response and recovery systems, Technologies: geospatial, knowledge management, AI systems, Social media, Institutional initiatives